1982
DOI: 10.1111/j.1532-5415.1982.tb07100.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Caffeine in Elderly Men

Abstract: Ten healthy elderly male volunteers were given 4 mg/kg of caffeine by intravenous infusion on three separate occasions. This resulted in mean peak plasma concentrations of caffeine of 7.4 +/- 0.7 micrograms/ml. Immediately after each of the three caffeine infusions, the mean systolic blood pressures increased 14, 7, and 16 mm Hg, and the mean diastolic blood pressures increased 7, 4, and 7 mm Hg, respectively. Both the systolic and the diastolic blood pressures returned to preinfusion values within 4 hours. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Thus, it is likely that this study underestimated the pressor response to caffeine in the older women. Our finding of increased SBP and DBP following caffeine ingestion corroborates previous investigations in younger and older men (Arciero et al 1995(Arciero et al , 1998Conrad et al 1982;Haigh et al 1993;Keogh and Witt 2001;Lenders et al 1988). Although our subjects were not hypertensive, evidence exists to support the elevated pressor response to caffeine in hypertensive and normotensive subjects (Rogers et al 2008;Hartley et al 2001Hartley et al , 2004Sung et al 1994), although this finding is not universal .…”
Section: Blood Pressure Heart Rate and Caffeinesupporting
confidence: 94%
“…Thus, it is likely that this study underestimated the pressor response to caffeine in the older women. Our finding of increased SBP and DBP following caffeine ingestion corroborates previous investigations in younger and older men (Arciero et al 1995(Arciero et al , 1998Conrad et al 1982;Haigh et al 1993;Keogh and Witt 2001;Lenders et al 1988). Although our subjects were not hypertensive, evidence exists to support the elevated pressor response to caffeine in hypertensive and normotensive subjects (Rogers et al 2008;Hartley et al 2001Hartley et al , 2004Sung et al 1994), although this finding is not universal .…”
Section: Blood Pressure Heart Rate and Caffeinesupporting
confidence: 94%
“…This study showed that systolic (SBP) and diastolic (DBP) blood pressure increased signi®cantly following caffeine ingestion and persisted until the termination of the study only in older men. Our ®nding of increased SBP and DBP response in healthy normotensive older men following caffeine ingestion has been corroborated by others (Conrad et al, 1982;Lenders et al, 1988;Haig et al, 1993). It is important to note that our older subjects were normotensive, as most previous research supports an elevated pressor response to caffeine in hypertensive patients (Smits et al, 1986;Sung et al, 1994;Pincomb et al, 1996), although this ®nding is not universal .…”
Section: Blood Pressure and Caffeinesupporting
confidence: 88%
“…The pressor effect of caffeine has been attributed to local antagonism of adenosine-mediated vasodilation (Smits et al, 1987) and increased sympathetic nervous system activity (Robertson et al, 1978). The ®ndings from our previous study (Arciero et al, 1995), as well as others (Izzo et al, 1983;Poehlman et al, 1989;Conrad, et al, 1982), do not support a role for undifferentiated sympathetic nervous system stimulation due to little or no increase in plasma norepinephrine following caffeine administration, and the ®nding of no difference in baseline or caffeine-stimulated norepinephrine kinetics in either of the two groups (Arciero et al, 1995). Epinephrine release from the adrenal medulla may have contributed to the increased SBP, but not DBP, response to caffeine observed in our older subjects (Conrad et al, 1982).…”
Section: Blood Pressure and Caffeinementioning
confidence: 64%
“…A transient increase in blood pressure was seen in healthy elderly men after an intravenous infusion of caffeine [Conrad et al 1982]. This study was however confounded by the lack of a placebo control and did not assess the effects of chronic caffeine use or duration of abstention on the acute response.…”
Section: Introductionmentioning
confidence: 89%